Influence of the adsorption geometry of PTCDA on Ag(111) on the tip–molecule forces in non-contact atomic force microscopy - Langewisch, Gernot; Falter, Jens; Schirmeisen, André; Fuchs, Harald (Beilstein Journal of Nanotechnology, 2014)
Perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) adsorbed on a metal surface is a prototypical organic–anorganic interface. In the past, scanning tunneling microscopy and scanning tunneling spectroscopy studies of PTCDA adsorbed on Ag(111) have revealed differences in the electronic structure of the molecules depending on their adsorption geometry. In the work presented here, high-resolution 3D force spectroscopy measurements at cryogenic temperatures were performed on a surface area that contained a complete PTCDA unit cell with the two possible geometries. At small tip-molecule separations, deviations in the tip-sample forces were found between the two molecule orientations. These deviations can be explained by a different electron density in both cases. This result demonstrates the capability of 3D force spectroscopy to detect even small effects in the electronic properties of organic adsorbates.
Keywords: atomic force microscopy; organic molecules; three-dimensional (3D) force spectroscopy

(untitled) - Tautz, F. S. (Prog. Surf. Sci., 2007)

(untitled) - Umbach, E.; Glöckler, K.; Sokolowski, M. (Surf. Sci., 1998)

(untitled) - Braun, D.-A.; Schirmeisen, A.; Fuchs, H. (Surf. Sci., 2005)

(untitled) - Kraft, A.; Temirov, R.; Henze, S. K. M.; Soubatch, S.; Rohlfing, M.; Tautz, F. S. (Phys. Rev. B: Condens. Matter Mater. Phys., 2006)

(untitled) - Rohlfing, M.; Temirov, R.; Tautz, F. S. (Phys. Rev. B: Condens. Matter Mater. Phys., 2007)

(untitled) - Such, B.; Weiner, D.; Schirmeisen, A.; Fuchs, H. (Appl. Phys. Lett., 2006)

(untitled) - Braun, D.-A.; Weiner, D.; Such, B.; Fuchs, H.; Schirmeisen, A. (Nanotechnology, 2009)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Mohn, F.; Gross, L.; Moll, N.; Meyer, G. (Nat. Nanotechnol., 2012)

(untitled) - Baykara, M. Z.; Schwendemann, T. C.; Altman, E. I.; Schwarz, U. D. (Adv. Mater., 2010)

(untitled) - Albrecht, T. R.; Grütter, P.; Horne, D.; Rugar, D. (J. Appl. Phys., 1991)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 2000)

(untitled) - Langewisch, G.; Falter, J.; Fuchs, H.; Schirmeisen, A. (Phys. Rev. Lett., 2013)

(untitled) - Hölscher, H.; Langkat, S. M.; Schwarz, A.; Wiesendanger, R. (Appl. Phys. Lett., 2002)

(untitled) - Sader, J. E.; Jarvis, S. P. (Appl. Phys. Lett., 2004)

(untitled) - Moll, N.; Gross, L.; Mohn, F.; Curioni, A.; Meyer, G. (New J. Phys., 2012)

(untitled) - Langewisch, G.; Kamiński, W.; Braun, D.-A.; Möller, R.; Fuchs, H.; Schirmeisen, A.; Pérez, R. (Small, 2012)

(untitled) - Baykara, M. Z.; Dagdeviren, O.; Schwendemann, T. C.; Mönig, H.; Altman, E. I.; Schwarz, U. D. (Beilstein J. Nanotechnol., 2012)